Proceedings of the 51st Annual ACM SIGACT Symposium on Theory of Computing 2019
DOI: 10.1145/3313276.3316342
|View full text |Cite
|
Sign up to set email alerts
|

Achieving optimal backlog in multi-processor cup games

Abstract: The single-and multi-processor cup games can be used to model natural problems in areas such as processor scheduling, deamortization, and buffer management.At the beginning of the single-processor cup game, n cups sit in a row, initially empty. In each step of the game, a filler distributes 1 unit of water among the cups, and then an emptier selects a cup and removes 1 + ε units from that cup. The goal of the emptier is to minimize the amount of water in the fullest cup, also known as the backlog. It is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 39 publications
(94 reference statements)
0
53
0
Order By: Relevance
“…For fixed p, and as n grows large, this becomes backlog O(log log n), which is known to be asymptotically optimal. As noted by Bender et al [9], any analysis of the smoothed greedy algorithm also doubles as a smoothed analysis for the deterministic greedy algorithm. This is because the smoothed greedy algorithm works by first randomly perturbing the initial starting state of the game, and then following a variant of the standard deterministic greedy algorithm on the perturbed game.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…For fixed p, and as n grows large, this becomes backlog O(log log n), which is known to be asymptotically optimal. As noted by Bender et al [9], any analysis of the smoothed greedy algorithm also doubles as a smoothed analysis for the deterministic greedy algorithm. This is because the smoothed greedy algorithm works by first randomly perturbing the initial starting state of the game, and then following a variant of the standard deterministic greedy algorithm on the perturbed game.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Bender et al [9] showed that as long as δ ≥ 1 poly(n) , the greedy emptying algorithm achieves backlog O( 1 ǫ log n). When ǫ ≥ Ω(1), this results in an asymptotically optimal backlog of O(log n).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations